Patterns of injuries among 160 Brazilian competitive tennis players - Teixeira, R. (2000)
A retrospective study was conducted among 160 competitive amateur tennis players from the Sao Paulo Tennis Federation of Brazil, to analyze the patterns of the lesions that occurred during their tennis careers. A questionnaire was mailed to the players. The inclusion criteria for the study were membership of the Federation and participation in tournaments for at least one year. The players were asked about the type of lesions that occurred during games, the number of days for which they were unable to play as a result, the types of racquet used and the tension of the strings during play. Respondents were divided into four age groups and injury patterns were compared. A total of 244 lesions were reported in 122 players. The average incidence was 0.16 lesions per athlete per year of tournament play. Muscular lesions were reported by 58 players (23.8%). A total of 48 players (19.7%) suffered from foot and ankle injuries and a further 41 (16.8%) from elbow lesions. In the latter group, tennis elbow was the most common type of lesion (38 players, or 15.6%). 36 of the 122 athletes suffered ankle sprains and 21 (8.6%) reported a supraspinatus tear. No correlation was found between the type of the racquet and the tension of the strings in a comparison of players with and without tennis elbow. The mean time away from the courts as a result of injury was 41 days. In our experience, physicians need to focus more attention on the study of lesions caused by tennis. In particular, preventive techniques for tennis elbow require closer study, in order to avoid worsening of the damage for athletes.